COMPARISON OF THE ACCURACY OF ULTRASONOGRAPHY AND CONVENTIONAL RADIOGRAPHY IN DETECTING FRACTURES IN INDIVIDUALS WHO HAVE A CLINICAL SUSPICION - Sadia Naseer Qazi,; Adil Qyyum,; Nisar Ahmed,; Ruqqia Adil, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Fracture detection plays a crucial role in clinical settings, influencing patient management and treatment decisions. Traditional methods, such as conventional radiography, have been the standard for fracture imaging. However, with advancements in technology, ultrasonography has emerged as a potential alternative, offering benefits such as portability and the absence of ionizing radiation. This study aims to compare the accuracy of ultrasonography and conventional radiography in identifying fractures in individuals presenting with clinical suspicion. The primary objective of this study is to assess and compare the diagnostic accuracy of ultrasonography and conventional radiography in detecting fractures. By evaluating both imaging modalities, we aim to provide insights into the potential utility of ultrasonography as a viable option for fracture diagnosis, particularly in cases where conventional radiography may present limitations. Methods: This prospective comparative study involves individuals with a clinical suspicion of fractures, who will undergo both ultrasonography and conventional radiography. The imaging results will be independently assessed by experienced radiologists blinded to the clinical information. Sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy will be calculated for both modalities. Statistical analyses, including paired t-tests, will be employed to determine significant differences between the two methods. Results: Preliminary results indicate that ultrasonography demonstrates comparable accuracy to conventional radiography in detecting fractures. Sensitivity, specificity, and overall accuracy will be presented, highlighting the strengths and limitations of each imaging modality. Any statistically significant differences between the two methods will be discussed in detail. Conclusion: This study contributes valuable insights into the comparative accuracy of ultrasonography and conventional radiography in fracture detection among individuals with clinical suspicion. The findings aim to guide healthcare professionals in making informed decisions regarding the choice of imaging modality based on the clinical context and available resources.